2004
DOI: 10.2460/javma.2004.224.562
|View full text |Cite
|
Sign up to set email alerts
|

Association between cribbing and entrapment of the small intestine in the epiploic foramen in horses: 68 cases (1991–2002)

Abstract: Results suggest that there may be an association between cribbing and EFE in horses, with horses with a history of cribbing more likely to have EFE than horses without such a history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 19 publications
5
48
0
1
Order By: Relevance
“…A previous study showed a much higher prevalence of cribbing in horses with EFE compared to horses with other strangulating small intestinal lesions (Archer et al . 2004).…”
Section: Discussionmentioning
confidence: 92%
“…A previous study showed a much higher prevalence of cribbing in horses with EFE compared to horses with other strangulating small intestinal lesions (Archer et al . 2004).…”
Section: Discussionmentioning
confidence: 92%
“…Owners of horses who crib‐bite are already warned that crib‐biting leads to excessive incisor wear (Houpt 1986), and has been linked to weight loss, gastric or gastroduodenal ulceration (Nicol et al . 2002), gas colic (White 1997), epiploic foramen entrapment (Archer et al . 2004), large colon impactions (Hillyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…2008) and are at greater risk of developing simple colonic obstruction distension colic (Hillyer et al. 2002) and epiploic foramen entrapment (Archer et al. 2004, 2008) compared to non‐crib‐biting/windsucking horses.…”
Section: Introductionmentioning
confidence: 99%